Control efficacy of Ca‐containing foliar fertilizers on bitter pit in bagged 'Fuji' apple and effects on the Ca and N contents of apple fruits and leaves. (14th June 2018) - Yu, Xian‐Mei; Wang, Jin‐Zheng; Nie, Pei‐Xian; Xue, Xiao-Min; Wang, Gui‐Ping; An, Miao
Abstract: BACKGROUND: The preharvest application of Ca‐containing foliar fertilizers can reduce the incidence of bitter pit (BP) in apples and improve fruit quality by increasing the Ca content and decreasing both the N content and the N/Ca ratio in fruits. In this study, we aimed to investigate the control efficacy of Ca‐containing fertilizers on the incidence of BP and their effects on the Ca and N contents in bagged 'Fuji' apples by spraying foliar fertilizer containing calcium chloride (CaCl2 ), calcium nitrate [Ca(NO3 )2 ] or calcium formate [Ca(HCOO)2 ] at an early stage, five days after full bloom (DAFB) and 40 DAFB, and at a late stage, 80 DAFB and 125 DAFB. RESULTS: The incidences of BP were reduced significantly by 43.2–73.0%, and the efficacy of spraying at an early stage was significantly higher than that of spraying at a late stage. The Ca content of bagged apple fruits increased whereas the N content and N/Ca ratio decreased after spraying Ca‐containing foliar fertilizers; however, the Ca content, N content and N/Ca ratio of apple leaves were differentially influenced. CONCLUSION: Foliar fertilizer containing CaCl2, Ca(NO3 )2 or Ca(HCOO)2 can be used at an early stage to control BP in apple and improve the quality of bagged apple fruits. © 2018 Society of Chemical Industry